Identification of sennoside A as a novel inhibitor of the slingshot (SSH) family proteins related to cancer metastasis. (May 2017) - Lee, Seon Young; Kim, Wooil; Lee, Young Geun; Kang, Hyo Jin; Lee, Sang-Hyun; Park, Sun Young; Min, Jeong-Ki; Lee, Sang-Rae; Chung, Sang J.
Graphical abstract: Abstract: Phospho-cofilin ( p -cofilin), which has a phosphate group on Ser-3, is involved in actin polymerization. Its dephosphorylated form promotes filopodia formation and cell migration by enhancing actin depolymerization. Protein phosphatase slingshot homologs (SSHs), known as dual-specificity phosphatases, catalyze hydrolytic removal of the Ser-3 phosphate group from phospho-cofilin. Aberrant SSH activity results in cancer metastasis, implicating SSHs as potential therapeutic targets for cancer metastasis. In this study, we screened 658 natural products purified from traditional oriental medicinal plants to identify three potent SSH inhibitors with submicromolar or single-digit micromolar K i values: gossypol, hypericin, and sennoside A. The three compounds were purified from cottonseed, Saint John's wort, and rhubarb, respectively. Sennoside A markedly increased cofilin phosphorylation in pancreatic cancer cells, leading to impaired actin dynamics in pancreatic cancer cells with or without EGF stimulation and reduced motility and invasiveness in vitro and in vivo . Collaboratively, these results demonstrate that sennoside A is a novel inhibitor of SSHs and suggest that it may be valuable in the development of pharmaceutical drugs for treating cancer metastasis.